Converting Dissertation to Journal Article: Why and How? - Nayak, Chaturbhuja (Homœopathic Links, 2021)
Research work embodied in a master's dissertation remains confined to a limited domain of the researcher, supervisor/co-supervisor and university library. It is desirable that the dissertation material be published in a reputed journal for various reasons including career growth of the researcher, recognition by the professional body, dissemination to a wider audience etc. Writing a research article from a dissertation does not mean just to shorten the latter mechanically or a cut-paste method. For the novice writer, it is a daunting task, but rewarding experience as well, to convert a dissertation to an article. Advice and support of the supervisor and senior colleagues having good experience in research as well as publication should be taken who can navigate the publication process, following the guidelines of the target journal. This article presents a synthesis of guidelines and practices to be followed by the researchers to see that the outcomes of their incessant and tireless efforts in preparing the dissertations be documented through publishable articles.
Keywords: dissertation; journal article; dissertation to article; purpose; method